Who cares about workplace justice in Barbados? Men and women have their say - a preliminary analysis - Nurse, Lawrence (2002)
Ascertains whether gender makes a difference to workers' perceptions about the justice of outcomes that result from the practice of workplace relations in Barbados. Reviews gender-based experiences with and perceptions of grievance management, performance appraisal and promotions practice. Examines gender-based perceptions of justice from three perspectives viz. distributive, procedural and interactional.